TEACHING MATERIALS AS TOOLS TO REPRESENT EDUCATIONAL STANDARTS AND NATIONAL VALUES. SUITABILITY OF TEACHING MATERIALS AND TEACHING SYLLABUS (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Annotation: This article discusses the pivotal role of teaching materials and syllabi in representing educational standards and promoting national values. It emphasizes the alignment of teaching materials with educational objectives and the incorporation of cultural narratives to instill a sense of national identity and civic responsibility. Furthermore, it underscores the importance of assessing the suitability of teaching materials in terms of relevance, inclusivity, and pedagogical effectiveness.